2008
DOI: 10.1111/j.1467-6494.2008.00493.x
|View full text |Cite
|
Sign up to set email alerts
|

Secure Versus Fragile High Self‐Esteem as a Predictor of Verbal Defensiveness: Converging Findings Across Three Different Markers

Abstract: Why is it that many individuals verbally rationalize and distort self-esteem threatening information? We examined whether such verbal defensiveness (Feldman Barrett, Williams, & Fong, 2002) differs as a function of whether individuals' high self-esteem is secure or fragile. Our findings indicated that individuals whose self-esteem was stable, not contingent, or congruent with high implicit self-esteem exhibited especially low amounts of verbal defensiveness. In contrast, verbal defensiveness was considerably h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
151
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(161 citation statements)
references
References 98 publications
(140 reference statements)
5
151
0
5
Order By: Relevance
“…Studies have shown that people with so-called defensive high self-esteem display defensive self-enhancement, manifesting as unrealistic optimism, reduction of distance between actual and ideal self, and preference for excessively positive feedback (Bosson, Brown, Zeigler-Hill, & Swann, 2003;Jordan, Spencer, & Zanna, 2005;Schrooder-Abe, Rudolph & Schutz, 2007). They also have weaker abilities to selfregulate emotions following failure compared to people with so-called secure high self-esteem (Kernis, Lakey, & Heppner, 2008;Lambird & Mann, 2006;McGregor & Marigold, 2003). Defensive high self-esteem is recognized by the coexistence of high explicit selfesteem (ESE) and low implicit self-esteem (ISE) (Jordan, Spencer, Zanna, Hoshino-Browne, & Correll, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that people with so-called defensive high self-esteem display defensive self-enhancement, manifesting as unrealistic optimism, reduction of distance between actual and ideal self, and preference for excessively positive feedback (Bosson, Brown, Zeigler-Hill, & Swann, 2003;Jordan, Spencer, & Zanna, 2005;Schrooder-Abe, Rudolph & Schutz, 2007). They also have weaker abilities to selfregulate emotions following failure compared to people with so-called secure high self-esteem (Kernis, Lakey, & Heppner, 2008;Lambird & Mann, 2006;McGregor & Marigold, 2003). Defensive high self-esteem is recognized by the coexistence of high explicit selfesteem (ESE) and low implicit self-esteem (ISE) (Jordan, Spencer, Zanna, Hoshino-Browne, & Correll, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It is broadly accepted that self-esteem is a multi-dimensional construct (Kernis, Lakey & Heppner, 2008). Specific aspects of self-esteem that have been put forward include contingent self-esteem, self-esteem instability and implicit self-esteem.…”
Section: Self-esteem As a Potential Moderator Self-affirmation Researchmentioning
confidence: 99%
“…Contingent self-esteem reflects the extent to which an individual bases their self-esteem on external factors, such as performance outcomes and approval from other people (Zeigler-Hill, Besser & King, 2011). In particular, while individuals with low levels of contingent self-esteem have a secure sense of self-worth that is not dependent on external factors, individuals with high levels of contingent self-esteem rely on continual external validation in order to maintain feelings of self-worth (Kernis, Lakey & Heppner, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the former case, the contingencies of self-esteem may be more tangible. This could explain why self-reported contingency is typically higher among participants with low self-esteem (r = -.51 in the study by Kernis et al, 2008). Having experienced that their self-esteem can suffer blows and is threatened by disapproval or failure, people with low self-esteem may simply be more aware of these contingencies.…”
mentioning
confidence: 85%